1995
DOI: 10.1007/bf01189060
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged axonal survival in transected nerves of C57BL/Ola mice is independent of age

Abstract: Interrupted nerve fibres from the C57BL/Ola strain of mouse degenerate after an extraordinary delay compared to nerves of standard laboratory mice. Other investigators, using electrophysiologic methods, concluded that the mutant phenotype diminishes with age, implying that the mutation in C57BL/Ola mice affects a developmentally regulated gene. In an effort to confirm this observation, we studied the course of Wallerian degeneration in C57BL/Ola mice aged 1 through 16 months by using quantitative morphometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…To put this low stringency in perspective, most axons in Wld S homozygotes survive structurally even 14 days after lesioning. 6,15,23,24 First, we studied 3-day lesioned distal nerve stumps using electron microscopy ( Figure 3 and Supplementary Figure 3). In Wld S heterozygotes, most axons displayed normal cytoskeleton, unswollen mitochondria and a regular myelin sheath of normal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…To put this low stringency in perspective, most axons in Wld S homozygotes survive structurally even 14 days after lesioning. 6,15,23,24 First, we studied 3-day lesioned distal nerve stumps using electron microscopy ( Figure 3 and Supplementary Figure 3). In Wld S heterozygotes, most axons displayed normal cytoskeleton, unswollen mitochondria and a regular myelin sheath of normal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…No protection was seen in the SOD1 G37R or SOD1 G85R mice [51] . This result could be explained by the observation that the Wld S protective phenotype only lasts 2-3 weeks after injury [52] , and is diminished after 3 months of age at the most terminal portions of the axon [53] . Therefore, Wld S may be more effective in acute processes or in early-onset disease, such as pmn, and protection may be lost in chronic disease models [48] .…”
Section: Axonal Degeneration Is Independent Of Cell Deathmentioning
confidence: 91%
“…Although one study showed that the prolonged survival of axons in transected nerves of Wlds mice is independent of age, 91 most other studies found that the Wlds phenotype is age-dependent. One study showed that although the expression of Wlds protein was independent of age in these mice, loss of ability of the sciatic nerve to conduct action potentials after transection is much more rapid in mice one year of age when compared to one month old animals.…”
Section: Age Nad and Neural Protectionmentioning
confidence: 98%